Determination of Corporate Image, Buyer-Supplier Relationship and Marketing Communication on Supplier Performance and its Implications on Customer Trust in Bumd DKI Jakarta - Hasrul, Hasrul; Muharam, Hari; Limankrisna, Nandan (International Journal Labs, 2025)
DKI Jakarta's BUMDs face significant challenges, including financial instability and declining customer trust, threatening their role in regional development. This study aims to analyze the direct and indirect effects of corporate image, buyer-supplier relationships, and marketing communication on supplier performance and customer trust. Using SEM analysis with data from 400 respondents, the research reveals that all three factors positively and significantly influence supplier performance and customer trust, both directly and indirectly, with supplier performance acting as a partial mediator. Key findings indicate that marketing communication has the strongest impact on supplier performance (path coefficient: 0.55), while supplier performance significantly enhances customer trust (path coefficient: 0.47). The study underscores the importance of holistic strategies to strengthen corporate image, supplier relationships, and communication to rebuild trust and operational efficiency in BUMDs. These findings contribute to the literature on public-sector supply chain management and offer practical implications for policymakers and BUMD leaders to foster sustainable development through improved stakeholder engagement.